STRUCTURAL AND CHARACTERIZATION POLYACRYLONITRILE NANOFIBER FOR AIR FILTRATION ASSEMBLED BY ELECTROSPINNING - Mataram, Agung; Ismail, A.F. (Prosiding Seminar Nasional Sains Dan Teknologi Fakultas Teknik, 2011)
In electrospinning, the structure of nanofibers, which is affected by polymer solution parameters and processing conditions, influences the physical characteristics of nanofiber mats. In this study, under optimum conditions of electrospinning, the concentration of polyacrylonitrile (PAN) was changed 14, 16 and 18 wt %, and its effects on the nanofiber diameter and pore size of nanofiber mats were studied. The results showed that increasing the PAN polymer concentration enhanced the nanofiber diameter and pore diameter of nanofiber mats. Keywords: electrospinning; concentrations; pore size